2016
DOI: 10.1016/j.ijpharm.2016.01.024
|View full text |Cite
|
Sign up to set email alerts
|

Diclofenac-β-cyclodextrin for colonic drug targeting: In vivo performance in rats

Abstract: The aim of this in vivo study was to assess the ability of the prodrug conjugate diclofenac-β-cyclodextrin to release diclofenac in the colon following oral administration, using sulfapyridine (a metabolite of sulfasalazine) as a marker of colonic absorption. Two groups of rats were used; the test rats received a suspension containing the two prodrugs, diclofenac-β-cyclodextrin and sulfasalazine, while the control rats received a suspension containing the corresponding free drugs, sodium diclofenac and sulfapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Various analytical techniques have been reported for the quantification of diclofenac sodium (DS) in different matrices. High-pressure liquid chromatography detection (HPLC) is the most common used method for the determination of DS in biological sample or dosage forms (Bhattacharya et al, 2013, Klimeš et al, 2001, Yan et al, 2014, Vieira et al, 2016, Mahdi et al, 2016, Cordery et al, 2017, Khan et al, 2016, Pireddu et al, 2015, Aldwaikat and Alarjah, 2015, Hegazy et al, 2015, Kasperek, 2008, Basusarkar, 2011, Nivsarkar et al, 2015, Korodi et al, 2012, Chaudhary et al, 2011, Kubala et al, 1993, Mulgund et al, 2009, Gaudiano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Various analytical techniques have been reported for the quantification of diclofenac sodium (DS) in different matrices. High-pressure liquid chromatography detection (HPLC) is the most common used method for the determination of DS in biological sample or dosage forms (Bhattacharya et al, 2013, Klimeš et al, 2001, Yan et al, 2014, Vieira et al, 2016, Mahdi et al, 2016, Cordery et al, 2017, Khan et al, 2016, Pireddu et al, 2015, Aldwaikat and Alarjah, 2015, Hegazy et al, 2015, Kasperek, 2008, Basusarkar, 2011, Nivsarkar et al, 2015, Korodi et al, 2012, Chaudhary et al, 2011, Kubala et al, 1993, Mulgund et al, 2009, Gaudiano et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…This enhancer effect of TM in the lipid bilayer was exhibited in the in vitro release profiles, showing the same relationship as the permeation behavior. Therefore, it can be concluded from the study that the optimized formulation could act as an enhancer of permeation for Acz and TM because of the presence of a lipophilic structure, cationic charge, and HPβCD, according to other authors [96].…”
Section: Discussionmentioning
confidence: 76%
“…Promising results were shown after clinical trials of KLEPTOSE CRYSMEB and 2‐HP‐β‐CD‐based therapy as cholesterol‐chelating agent in atherosclerosis and Niemann‐Pick type C disease (Coisne et al, ). β‐CD‐based inclusion complexes for targeted drug delivery system incorporating aspirin (Ma et al, ) and diclofenac (Vieira et al, ) have been demonstrated. Advantages of modified β‐CDs as brain delivery vectors for RNAi‐based therapies in Huntington's disease were investigated (Godinho, Ogier, Darcy, O'Driscoll, & Cryan, ).…”
Section: In Drug Delivery Systemsmentioning
confidence: 99%
“…Promising results were Clonazepam Me-β-CD Liposomal and microemulsion formulations contain drug-CD complex showed greater solubility and permeation Mura, Bragagni, Mennini, Cirri, and Maestrelli (2014) Curcumin HP-β-CD Increases solubility, transdermal permeation of curcumin, and demonstrated better anti-inflammatory effect Ghanghoria, Kesharwani, Agashe, and Jain (2013) Diclofenac sodium HP-β-CD HP-β-CD grafted polyethyleneimine has proved as a potent skin penetration enhancer with no toxicity or skin irritation Yan et al (2014) Epalrestat ME-β-CD Enhanced dissolution and skin permeation through hairless mouse skin Furuishi et al (2017) Flurbiprofen HP-β-CD Polymeric nanospheres with drug-CD complex showed greater retention of drug in skin as well as stronger anti-inflammatory effect Vega et al (2013) Isotretinoin HP-β-CD Elastic liposomes significantly increased the skin deposition, prolonged drug release and reduce skin irritation Kaur, Puri, and Jain (2010) Itraconazole HP-β-CD Deformable liposomes contain drug-CD complex showed greater cutaneous drug deposition Alomrani, Shazly, Amara, and Badran (2014) Levodopa β-CD Stability of levodopa was enhanced when complexed with β-CD in transdermal patches Obaidat, Al-Shar'i, Tashtoush, and Athamneh (2016) Lornoxicam HP-β-CD Incorporation of CD and propylene glycol in gel improved the skin permeation Al-Suwayeh, Taha, Al-Qahtani, Ahmed, and Badran (2014) Propofol SBE-β-CD Complexation significantly improved the passive and iontophoretic transdermal flux Juluri, Peddikotla, Repka, and Murthy (2013) Terbinafine HP-β-CD Demonstrated the potential of CD as a transungual permeation enhancer Chouhan and Saini (2014) shown after clinical trials of KLEPTOSE CRYSMEB and 2-HP-β-CDbased therapy as cholesterol-chelating agent in atherosclerosis and Niemann-Pick type C disease (Coisne et al, 2016). β-CD-based inclusion complexes for targeted drug delivery system incorporating aspirin (Ma et al, 2015) and diclofenac (Vieira et al, 2016) have been demonstrated. Advantages of modified β-CDs as brain delivery vectors for…”
Section: Drug Targetingmentioning
confidence: 99%